2008
DOI: 10.1093/sleep/31.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Stabilizing Effects of E-6199, Compared to Zopiclone, Zolpidem and THIP in Mice

Abstract: Our findings demonstrate that E-6199 may be an effective hypnotic compound that promotes and improves NREMS, without producing EEG side effects, tolerance or withdrawal phenomena, when administered under chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 35 publications
10
28
0
Order By: Relevance
“…Examples of the primary EEG/EMG recordings for saline-and zolpidem-injected C57BL/6 (␥2F77) and ␥2I77 lox mice are shown in Figure 2. In agreement with previous studies (Kopp et al, 2004;Alexandre et al, 2008), we found that the power of "NREM sleep" produced by zolpidem in C57BL/6J mice was lower than that found in natural NREM sleep. Zolpidem reduced power during NREM sleep (Fig.…”
Section: Zolpidem Does Not Induce Sleep In ␥2i77supporting
confidence: 93%
See 4 more Smart Citations
“…Examples of the primary EEG/EMG recordings for saline-and zolpidem-injected C57BL/6 (␥2F77) and ␥2I77 lox mice are shown in Figure 2. In agreement with previous studies (Kopp et al, 2004;Alexandre et al, 2008), we found that the power of "NREM sleep" produced by zolpidem in C57BL/6J mice was lower than that found in natural NREM sleep. Zolpidem reduced power during NREM sleep (Fig.…”
Section: Zolpidem Does Not Induce Sleep In ␥2i77supporting
confidence: 93%
“…The effect persisted until at least 90 min after injection. These data, reduced sleep latency and prolonged sleep time, are consistent with previous reports on zolpidem's action in C57BL/6J mice (Kopp et al, 2004;Alexandre et al, 2008). By contrast, there was no change in the sleep time above baseline in zolpidem-injected ␥2I77 lox mice (n ϭ 6 paired t test, t (5) ϭ 0.18, p ϭ 0.86; Fig.…”
Section: Zolpidem Does Not Induce Sleep In ␥2i77supporting
confidence: 92%
See 3 more Smart Citations